LANGUAGE ERRORS AT THE SYNTACTIC LEVEL IN SHORT STORY ESSAYS OF GRADE X HIGH SCHOOL STUDENTS - Widia Tamara; Andriani; Ibnu Hajar (RADJA PUBLIKA, 2024)
This study aims to determine language errors in the syntactic level in short story essays of class X students of SMAN 2 Lhokseumawe. This type of research is qualitative research. The result of this study shows that there are three language errors in the level of syntax in the short story essays of class X students of SMAN 2 Lhokseumawe in the field of phrases and two syntactic errors in the field of sentences. The errors in the field of phrases consist of: (1) improper word order, (2) improper use of prepositions, and (3) the influence of local language in language and writing. The syntax errors in the field of sentences include sentences that do not have a subject. These errors can occur due to factors such as (1) lack of application of Indonesian language use in communication, (2) lack of student interest in writing short story essays, and (3) the influence of mother tongue or regional language in language and writing.